The secret life of whitetails [videorecording (DVD)] - Griffen, Gary W.; Coyote, Peter (Griffen Productions : Janson Media, 2012)
White-tailed deer are one of the most adaptable large grazing mammals on earth. They are the products of countless generations of evolutionary fine tuning. More than 38 sub-species range from southern Canada to South America. Millions of years ago, whitetails crossed an ancient land bridge from Asia to Alaska. Over eons, the whitetail's elusive and wary behavior was forged by a changing cast of predators, from saber-toothed tigers, to wolves and mountain lions.